Vitamin D Level Status and Hypertension among Old Adult Iraqi People in Al Hillah City - Ismael Hasan Jawad1 , Hasan ALwan Baiee2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Vitamin D has different biological actions in the body . Vitamin D has the pleiotropic effects in multiple organ systems, and vitamin D deficiency was suggested to be associated with high blood pressure according to previous reports. Several interventional studies have examined the effect of vitamin D supplementation on high blood pressure patients Objective : to identify Vitamin D level and its correlate with hypertension among old adults. Methodology: This was across sectional descriptive observational study included convenient sample of elderly people in Hilla City ,Babylon province, the period of the study started from the first of January through August 2019, a pretested semi structured questionnaire was used to interview the participants who attended primary health centers after obtaining their verbal consents, the sample included( 300) old adult of both gender, serum level of Vitamin D was assessed by chemo immunoassay method, the blood pressure was measured single handy by the researcher using mercury sphygmomanometer to diagnose hypertension. Results: The study included 300 participants 83.0% of the study sample had either insufficiency or deficiency of Vitamin D level. Hypertensive people had significant Vitamin D Deficiency (both deficiency and insufficiency of vitamin D, 81% and 70% ) respectively as compared to normotensive participants , this difference was statistically significant p<0.05. Conclusion: there was a significant inverse relationship between vitamin D level and blood pressure.